The Interplay of Soft Power and Sharp Power in Sport Diplomacy: A Conceptual Framework - de Andrade e Silva Forte dos Santos, Niedja (2021)
This paper aims to deliver a conceptual framework for further studies on the analysis of soft power and sharp power within sport diplomacy. Developed from the international relations perspective, the research is framed by the neoliberal institutionalism theory and public diplomacy notion. The traditional literature review builds up the research design. Concepts of soft power, sharp power, and sport diplomacy are operationalized and underpins the analytical framework which is an outcome of this study and can support future developments. Besides indicating paths for further research, the conclusion summarizes how sport diplomacy has integrated actors, tactics, and tools, as well as resources of soft and sharp power making the interplay of them within sport diplomacy.